2008
DOI: 10.1021/bc700394s
|View full text |Cite
|
Sign up to set email alerts
|

A Doxorubicin Prodrug Activated by the Staudinger Reaction

Abstract: Much effort has been devoted to prodrug systems that effect drug release at the tumor through enzymatic action. To widen the scope of prodrug therapy, the use of the selective Staudinger reaction as prodrug activator, instead of relying on enzymatic action, was investigated. Doxorubicin was conjugated to a p-azidobenzyl trigger that is cleaved after reacting with the chemical activator, triphenylphosphine. The prodrug activation was confirmed in water, cell growth medium, and serum, using HPLC and LCMS. Next, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 15 publications
0
76
0
Order By: Relevance
“…It had been previously shown that the Tat peptide does not induce membrane leakage up to a concentrations of 20 uM, suggesting that the peptide building blocks and conjugate showed no toxicity to cells. 18,33 …”
Section: Resultsmentioning
confidence: 99%
“…It had been previously shown that the Tat peptide does not induce membrane leakage up to a concentrations of 20 uM, suggesting that the peptide building blocks and conjugate showed no toxicity to cells. 18,33 …”
Section: Resultsmentioning
confidence: 99%
“…An example is the use of abiotic bioorthgonal reactions to provoke drug activation (Figure 10A), in contrast to the traditional reliance on endogeneous processes such as hydrolysis or enzymatic cleavage (Figure 10B). In a relatively simple example, the reduction of an azide by phosphine (Brakel et al, 2008) has been used as the prodrug activator in vivo , producing the corresponding aromatic amine that releases the cytotoxic cargo by 1,6-benzylic fragmentation (Figure 10C). The Staudinger ligation was also used to trigger drug liberation by virtue of a similar process triggered by O-to-N acyl migration to the iminophosphorane intermediate in the Staudinger process (Figure 10D) (Azoulay et al, 2006).…”
Section: B Bioorthogonal Conjugation Strategies and Applicationsmentioning
confidence: 99%
“…Aminocoumarin antibiotics TOF (sinapinic) Chemoenzymatic formation of novel aminocoumarin antibiotics by the enzymes CouN1 and CouN7 (Fridman, et al, 2007) Chloramphenicol-neomycin conjugate TOF Bacteriophage links to neomycin to carry chloramphenicol to target (Yacoby, et al, 2007) TOF Doxorubicin prodrug Drug activated by Staudinger reaction (triphenylphosphine not toxic as used) (van Brakel, et al, 2008) Enzymatic attachment of GalNAc to peptide array on gold surface (Laurent, et al, 2008c) Mannose-decorated thioacetates TOF (norharmane)…”
Section: Antibioticsmentioning
confidence: 99%